2006
DOI: 10.1002/zoo.20107
|View full text |Cite
|
Sign up to set email alerts
|

Intake, utilization, and composition of browses consumed by the Sumatran rhinoceros (Dicerorhinus sumatrensis harissoni) in captivity in Sabah, Malaysia

Abstract: The significant threats to the fewer than 30 wild Dicerorhinus sumatrensis harrissoni, the Bornean sub-species of the Sumatran rhinoceros, are obvious and include poaching, habitat loss, and environmental changes. Subtle effects on population survival, however, include nutritional or other diseases, which affect morbidity and reproductive success. To address these issues and focus on animals within their natural range, this feeding trial and analysis characterizes the diet fed to the only three captive D. s. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Deposition of iron (Fe) in multiple organs of the animal is of particular concern, as it has been a common finding at necropsy of adults in captivity (Molenaar et al, 2008; Paglia & Tsu, 2012). Previous studies of nutrient intake of captive browsing rhinoceros reported findings of high dietary Fe in conjunction with copper (Cu) deficiencies (Dierenfeld et al, 2000, 2006). Low vitamin E concentrations have also been associated with captive diseases in this species; most notably, low vitamin E status has been suspected as a factor underlying the occurrence of hemolytic anemia (Dierenfeld et al, 1988; Sullivan et al, 2015).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Deposition of iron (Fe) in multiple organs of the animal is of particular concern, as it has been a common finding at necropsy of adults in captivity (Molenaar et al, 2008; Paglia & Tsu, 2012). Previous studies of nutrient intake of captive browsing rhinoceros reported findings of high dietary Fe in conjunction with copper (Cu) deficiencies (Dierenfeld et al, 2000, 2006). Low vitamin E concentrations have also been associated with captive diseases in this species; most notably, low vitamin E status has been suspected as a factor underlying the occurrence of hemolytic anemia (Dierenfeld et al, 1988; Sullivan et al, 2015).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Iron storage disease (ISD), the deposition of excess body iron into insoluble iron clusters in soft tissue, is a health concern in many species in captivity [ 1 , 2 ]. The Sumatran rhinoceros ( Dicerorhinus sumatrensis ) is one of two browsing rhinoceros species that have evolutionarily adapted to a low-iron diet and is hence susceptible to iron overload [ 3 ]. It has been speculated that the lack of browse diversity and/or environmental conditions such as low exercise level and absence of hemoparasites are associated with the elevated metrics of iron loading in captive Sumatran rhinoceroses, however, the underlying cause of disease and the differences in individual susceptibility to ISD remain unclear [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most captive diets consist of combinations of mixed hay and straw, pressed hay, concentrate pellets, produce, and fresh forages (grasses, branches, and leaves) [Von Houwald, ]. Captive recommendations to offer browses such that nutrient intake more closely matches natural forage consumption have been suggested, but concerns include acquiring appropriate quantities, and seasonal and nutritional variability in composition [Clauss et al, ; Dierenfeld, ; Dierenfeld et al, 1994, 2005, 2006].…”
Section: Introductionmentioning
confidence: 99%